Improvement of the teaching methods by the experience of reputable pedagogical instruments - Mamatyusupovna , Abduvakhabova Umida; Kamiljonovna , Akramova Takhmina; Ibrakhimovna, Daukaeva Khalida (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to the use of language perception methods, analytical approach, development of critical thinking in teaching foreign languages as a second foreign language and achieving success. The article substantiates the feasibility of using the design methodology for teaching a foreign language, shows the increased interest of students in applying this teaching method. By implementing educational projects, students learn to solve problems similar to those that they will encounter later in practical activities. This increases their motivation to learn a foreign language. In contrast to the traditional relationship between the teacher and the student according to the scheme "object of training - subject of training", in project-based learning, a partnership interaction is formed between the teacher and the student.